Whole grain diet for Feedlot Lambs - Gallo, Sarita Bonagurio; Merlin, Fernanda de Almeida; Macedo, Cassio Moreira de [UNESP]; Oliveira Silveira, Ricardo Dutra de (Elsevier B.V., 2014)
For a lamb feedlot system became competitive it is essential that an equilibrate nutrition and functional feeding management happens naturally. Therefore, this experiment has the objective to evaluate the efficiency of whole corn grain diet on lambs performance and carcass quality parameters and ruminal papillae development. During the experiment twenty Dorper/Santa Inescrossbred lambs were used, divided randomly in two treatments: control diet and whole grain diet. The experimental design was completely randomized design and data analysis done by SISVAR using the Tukey test at 5% of probability. No statistical differences were observed on the characteristics evaluated for performance and carcass as well as the length and width of ruminal papillae. The composition of the diet together with the weight gain potential of the lambs can explain the good average daily weight gain of 0.284 kg. The initial body condition average was 2.1 (thin) and improved at the end of the trial period achieving3.15 (normal). Carcass yield reached 46.24%, the results is between the range ideal for specialty meat breeds ranging from 40 to 50%. The carcass conformation, fat cover conformation and the thickness of subcutaneous fat found can be classified as medians. Also there was no difference in the characteristics of ruminal papillae. Thus, it is concluded that the use of whole grain diet did not influence the characteristics evaluated; and the choice of diet should be made with regard to profitability, simplicity of use and availability of forage in feedlot. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carcass conformation; Fat cover; Carcass yield; Production rates; Ruminal papillae